Enhancing Biodiversity Learning Outcomes of Fifth-Grade Students through PBL-Integrated Flashcards Media: A Development and Evaluation Study - Sasqia, Laely Ayu Candra; Isdaryanti, Barokah (FKIP Universitas Lampung, 2025)
Enhancing Biodiversity Learning Outcomes of Fifth-Grade Students through PBL-Integrated Flashcards Media: A Development and Evaluation Study. Objectives: This study aims to improve learning outcomes on biodiversity and non-biodiversity material in grade V students using flashcard media development integrated with the Project Learning model. Flashcard media is developed based on biodiversity and non-biodiversity material by the curriculum and by PBL learning steps that encourage student involvement in learning. Methods: This research is a type of research and development (R&D) by Borg and Gall. Data was collected using non-test techniques in the form of observation, interviews, needs questionnaires, validation questionnaires, response questionnaires, and test techniques in the form of student learning outcomes tests in the form of pretests and posttests. The data analysis used was qualitative and quantitative. The product development validation test was carried out by material expert validators and media experts. The subjects of this study were students of class V B SD Negeri Wates 01, Semarang City, who were selected by purposive sampling. Findings: This study's results showed that the material experts' product feasibility test scored 86.66%, and from media experts scored 95%, including in the “very feasible” category, to be tested. The t-test results (2-tailed) show the sig value. 0.00 <0.05 with an N-Gain score of 0.77, including in the “high” category. There is a significant difference and increase in the average learning outcomes of students before and after using flashcards. Conclusion: The use of flashcard media development integrated with the PBL model on biodiversity and non-biodiversity material can improve the learning outcomes of fifth-grade students of SD Negeri Wates 01, Semarang City. This research can be a reference for teachers to innovate and create interesting learning media. Keywords: learning outcomes, flashcard, problem-based learning.